Bad news, good news: Coverage and response asymmetries - Luca Gambetti; Nicolò Maffei-Faccioli; Sarah Zoi (Norges Bank, 2022)
We study the dynamic link between economic news coverage and the macroeconomy. We construct two measures of media coverage of bad and good unemployment figures based on three major US newspapers. Using nonlinear time series techniques, we document three facts: (i) there is no significant negativity bias in economic news coverage. Newspapers' asymmetric responsiveness to positive and negative unemployment shocks is entirely explained by their asymmetric effects on unemployment; (ii) consumption reacts to bad news, but not to good news; (iii) bad news is more informative to the agents and modifies their expectations more than good news.
hdl:11250/3030772
Keywords: C32; E32; 330; News Coverage; Agents' Information; Business Cycles; Asymmetry; Threshold-SVAR